2003
DOI: 10.3766/jaaa.14.1.4
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency (1000 Hz) Tympanometry in Normal Neonates

Abstract: The characteristics of high frequency (1000 Hz) acoustic admittance results obtained from normal neonates were described in this study. Participants were 170 healthy neonates (96 boys and 74 girls) aged between 1 and 6 days (mean = 3.26 days, SD = 0.92). Transient evoked otoacoustic emissions (TEOAEs), and 226 Hz and 1000 Hz probe tone tympanograms were obtained from the participants using a Madsen Capella OAE/middle ear analyser. The results showed that of the 170 neonates, 34 were not successfully tested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
136
15
31

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(210 citation statements)
references
References 32 publications
28
136
15
31
Order By: Relevance
“…Studies with the 1000Hz probe in neonates proved to be efficient in detecting middle ear alterations. [3][4][5] The 226Hz probe tone has been suggested in the literature as the frequency of choice to assess infants up to four months of age, because such probe would be less affected by maturity differences and also because tympanometry patterns are better interpreted in this frequency when compared to the higher frequencies. 6,7 However, in the literature, papers stress the need to be careful in carrying out this test in infants below seven months of age, because they may present a type A tympanometry curve, even when there is fluid in the middle ear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with the 1000Hz probe in neonates proved to be efficient in detecting middle ear alterations. [3][4][5] The 226Hz probe tone has been suggested in the literature as the frequency of choice to assess infants up to four months of age, because such probe would be less affected by maturity differences and also because tympanometry patterns are better interpreted in this frequency when compared to the higher frequencies. 6,7 However, in the literature, papers stress the need to be careful in carrying out this test in infants below seven months of age, because they may present a type A tympanometry curve, even when there is fluid in the middle ear.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding TPP, Ytm and ECV, a significant effect was observed on the ECV measurement for the 226-Hz probe tone and on the Ytm measurements at 1000 Hz, both of which were higher for males. In another study analyzing data from 1000-Hz tympanometry in neonates, the authors found type A curves in 92.2% of cases and DP curves in 1.2% of cases as well as statistically greater Ytm measurements for the right ear 22 . The data observed in these two studies…”
Section: Resultsmentioning
confidence: 99%
“…It is important to mention that the inclusion criteria involved newborns who had otoacoustic emissions, based on the assumption that, in general, the presence of TEOAEs suggests not only the normality in the cochlear amplifier mechanism, but also normal middle ear function, or close to normal. However, since there are reports in literature mentioning that conductive impairment did not influence the record of TEOAEs, or that resulted in reduced level of response (19,29) , only newborns who presented TEOAEs, tympanogram with one or two peaks for both probe tones were included in the study sample. These patterns are indicators of normal middle ear function for the newborn population.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there is no regulation for the research of acoustic reflex threshold in this population (19) ; some studies have tried to establish levels of ASRT for healthy newborns, by using different pure tones in broadband noise (BBN). Therefore, it is necessary to perform studies verifying the occurrence and threshold of acoustic reflex among newborns with different probe tones to generate the stimulus.…”
Section: Introductionmentioning
confidence: 99%